Settlement of Bad Credit that is Tied to Mortgage Guarantee by Voluntary Sale at Bank Rakyat Indonesia Padang Sidempuan Branch - Khoirunnisa, Nabila; Kamelo, Tan; Harianto, Dedi; Andrianti, Syarifah Lisa (PT FORMOSA CENDEKIA GLOBAL, 2023)
The method used in this research is normative juridical research. The results of the research found that the legal provisions for resolving bad credit which are tied to mortgage rights that are sold voluntarily are related to the execution of mortgage rights objects. Mechanisms and procedures for resolving bad debts tied to mortgage rights sold voluntarily at PT. BRI Padangsidimpuan Branch in problem loans, the bank can take two methods or strategies, namely credit rescue and credit settlement. Obstacles that arise in the process of executing this voluntary sale, when the execution occurs, the debtor changes his mind/is uncooperative and does not want the mortgage object to be sold immediately, the debtor is complicated in carrying out the execution through a voluntary sale to resolve bad credit.